Canadian Community College Counselling Services — How Are They Staffed? - Johnston, E. F.; Miles, F. A. (Canadian Journal of Counselling and Psychotherapy, 2012)
Because little is known about counselling services in Canadian community colleges, the authors sent questionnaires to 179 post-secondary,non-university, educational institutions and received replies from 83. Data on numbers of counselling personnel, their educational level, salaries, counsellor-student ratios, support staff, and other relevant material are reported.